2020
DOI: 10.1111/1462-2920.14996
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio splendidus O‐antigen structure: a trade‐off between virulence to oysters and resistance to grazers

Abstract: A major debate in evolutionary biology is whether virulence is maintained as an adaptive trait and/or evolves to non-virulence. In the environment, virulence traits of non-obligatory parasites are subjected to diverse selective pressures and trade-offs. Here, we focus on a population of Vibrio splendidus that displays moderate virulence for oysters. A MARTX (Multifunctional-autoprocessing repeats-in-toxin) and a type-six secretion system (T6SS) were found to be necessary for virulence toward oysters, while a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…The VirB/D system, a model of T4SS, and five components of T6SS (Hcp, DotU, VasA, VasK, TssA1) were found in the genomes of some of the members, in which Hcp protein was involved in the immune system evasion and biofilm formation in A. hydrophila (Rasmussen‐Ivey et al, 2016). Rubio et al (2019) showed that T6SS plays a critical role in the success of vibrio infections, and Oyanedel et al (2020) also showed the necessity of T6SS in the virulence of V. splendidus towards oysters, but more details of these SSs need to be explored at a future date.…”
Section: Resultsmentioning
confidence: 99%
“…The VirB/D system, a model of T4SS, and five components of T6SS (Hcp, DotU, VasA, VasK, TssA1) were found in the genomes of some of the members, in which Hcp protein was involved in the immune system evasion and biofilm formation in A. hydrophila (Rasmussen‐Ivey et al, 2016). Rubio et al (2019) showed that T6SS plays a critical role in the success of vibrio infections, and Oyanedel et al (2020) also showed the necessity of T6SS in the virulence of V. splendidus towards oysters, but more details of these SSs need to be explored at a future date.…”
Section: Resultsmentioning
confidence: 99%
“…demonstrated that the Vibrio population structure is seasonal and varies in oysters affected by POMS ( 27 ). Notably, Vibrio of the Splendidus clade are present in healthy oysters when no mortalities occur ( 27 ), but they only express low to moderate pathogenic potential in these circumstances ( 48 ). V. crassostreae is predominant during mortalities and is almost exclusively associated with oyster tissues ( 27 ).…”
Section: Poms Is a Polymicrobial Diseasementioning
confidence: 99%
“…They are more common in warmer coastal waters, especially above 17°C, and depending on the species, they tolerate a range of salinities (5–25 ppt; Ceccarelli et al ., 2019 ). Several Vibrio species have been associated with diseases in marine invertebrates (Wilson et al ., 2013 ), including oyster spat and/or larvae (Destoumieux‐Garzón et al ., 2020 ), and are associated with mortality outbreaks affecting the production of the Pacific oyster Crassostrea gigas worldwide (Lemire et al ., 2015 ; Vezzulli et al ., 2015 ; Bruto et al ., 2017 , 2018 ; Rubio et al ., 2019 ; Oyanedel et al ., 2020 ). In particular, Vibrio species belonging to the Splendidus clade have been repeatedly isolated from oysters suffering the ‘summer mortality syndrome’ and experimentally showed to cause death when injected to bivalves (Le Roux et al ., 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of virulence factors have been reported to cause disease, including cytolisin and secreted metalloproteases, many of them shared by phylogenetically coherent virulent population (Lemire et al ., 2015 ; Bruto et al ., 2017 ). Interestingly, it was recently reported that virulence potential in Vibrio populations may derive from the acquisition of ancestral genes such as the case of the R5.7 exported conserved protein within the Splendidus clade and the MARTX toxin cluster in Vibrio splendidus (Bruto et al ., 2018 ; Oyanedel et al ., 2020 ). According to the coincidental selection hypothesis factors responsible for virulence may have resulted from adaptation to other ecological niches other than the host.…”
Section: Introductionmentioning
confidence: 99%